2022
DOI: 10.3390/ijms231911001
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Active Diterpenoids in the Clerodendrum Genus—A Review

Abstract: One of the key areas of interest in pharmacognosy is that of the diterpenoids; many studies have been performed to identify new sources, their optimal isolation and biological properties. An important source of abietane-, pimarane-, clerodane-type diterpenoids and their derivatives are the members of the genus Clerodendrum, of the Lamiaceae. Due to their diverse chemical nature, and the type of plant material, a range of extraction techniques are needed with various temperatures, solvent types and extraction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…This study showed similar comparisons with various works of literature in citing these compounds as anticancer agents as such the compound Scutellarein and Scutellarein 7-glucuronide, flavones glycoside was reported to exhibit antiproliferative and antiapoptotic activities among various human malignancies [ 41 , 42 ]. Similarly, 17-hydroxyteuvincenone G showed significant cytotoxicities activities against the growth of human promyelocyticleukemia (HL-60) and human lung adenocarcinoma epithelial (A-549) tumor cell lines [ 43 ]. Teuvincenone A and E had remarkable in-vitro cytotoxicity activity against human cell lines [ 44 ], and acacetin exerts an antiproliferative effect by blocking cell cycle progression and could enhance the therapeutic potential in nonsmall cell lung cancer cell [ 45 ] and breast cancer [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study showed similar comparisons with various works of literature in citing these compounds as anticancer agents as such the compound Scutellarein and Scutellarein 7-glucuronide, flavones glycoside was reported to exhibit antiproliferative and antiapoptotic activities among various human malignancies [ 41 , 42 ]. Similarly, 17-hydroxyteuvincenone G showed significant cytotoxicities activities against the growth of human promyelocyticleukemia (HL-60) and human lung adenocarcinoma epithelial (A-549) tumor cell lines [ 43 ]. Teuvincenone A and E had remarkable in-vitro cytotoxicity activity against human cell lines [ 44 ], and acacetin exerts an antiproliferative effect by blocking cell cycle progression and could enhance the therapeutic potential in nonsmall cell lung cancer cell [ 45 ] and breast cancer [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Information on the chemical constituents of V. inermis (16) has been updated in this overview. The aerial part, leaf, stem, and root of the V. inermis plant (Figure 1) contain flavonoids (15), diterpenes/diterpenoids (12), sterols (10), triterpenes/triterpenoids (10), iridoid glycosides (9), phenolic glycosides (6), phenylethanoid glycosides (PEGs) (6), phenylpropanoid glycosides (PPGs) (4), and sesquiterpenes (2) (Table 1). There is only one phytochemical study on the flower of V. inermis.…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…Among species of the genus, pharmacological properties such as anti-inflammatory and antinociceptive, anti-oxidant, anti-hypertensive, anticancer, antimicrobial, anti-diarrheal, hepatoprotective, hypoglycemic, hypolipidemic, memory enhancing, and neuroprotective have been reported (4,5). Chemical constituents consist of a wide range of compounds, including flavonoids diterpenoids, triterpenoids, flavonoids, phenylethanoids, phenylpropanoids, and steroids (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Clerodendrum is one of the largest genera in the plant family Lamiaceae with approximately 500 species recorded to date. 1,2 It mostly consists of small trees, lianas, shrubs, woody vines, and rarely perennial or annual herbs which are widely distributed around the world. 1,2 The plants under this genus carry numerous therapeutic properties and thus have been utilized as traditional remedies for health disorders in their respective countries of origin.…”
mentioning
confidence: 99%
“…1,5 Diterpenes are the signature phytocompounds of this genus, particularly the abietane-, pimarane-, and clerodane-type diterpenoids which possess multiple bioactivities such as antiproliferative, antiinflammatory, antioxidant, and neuroprotective properties. 2 Clerodendrum polycephalum Baker is a flowering plant which can be found in tropical regions of Africa, South Asia, Cameroon, Ghana, Sierra Leone, and Guinea. 6,7 Little information is available regarding the chemistry of C. polycephalum, with only a few studies on the detection of its general constituents such as carbohydrates, tannins, flavonoids, alkaloids, saponins, and essential oil.…”
mentioning
confidence: 99%